Atomic Structural Evolution of Single‐Layer Pt Clusters as Efficient Electrocatalysts. Issue 26 (3rd June 2021) - Zhang, Bin‐Wei; Ren, Long; Xu, Zhong‐Fei; Cheng, Ning‐Yan; Lai, Wei‐Hong; Zhang, Lei; Hao, Weichang; Chu, Sheng‐Qi; Wang, Yun‐Xiao; Du, Yi; Jiang, Lei; Liu, Hua‐Kun; et al.
Abstract: The rational synthesis of single‐layer noble metal directly anchored on support materials is an elusive target to accomplish for a long time. This paper reports well‐defined single‐layer Pt (Pt‐SL) clusters anchored on ultrathin TiO2 nanosheets—as a new frontier in electrocatalysis. The structural evolution of Pt‐SL/TiO2 via self‐assembly of single Pt atoms (Pt‐SA) is systematically recorded. Significantly, the Pt atoms of Pt‐SL/TiO2 possess a unique electronic configuration with PtPt covalent bonds surrounded by abundant unpaired electrons. This Pt‐SL/TiO2 catalyst presents enhanced electrochemical performance toward diverse electrocatalytic reactions (such as the hydrogen evolution reaction and the oxygen reduction reaction) compared with Pt‐SA, multilayer Pt nanoclusters, and Pt nanoparticles, suggesting an efficient new type of catalyst that can be achieved by constructing single‐layer atomic clusters on supports. Abstract : Single‐layer Pt clusters, maintaining simultaneously adjacent Pt active atomic sites and PtPt covalent bonds, as a new frontier of atomic structure catalysts, are achieved by single Pt atoms self‐assembly. It exhibits unprecedented activity and stability toward diverse electrochemical reactions, such as hydrogen reduction reaction, oxygen reduction reaction, oxygen evolution reaction, and alcohol electrooxidation.